Fabrication, Microstructure, and Microhardness at High Temperature of In Situ Synthesized Ti3Al/Al2O3 Composites - Do Thanh Binh; Tran Duc Huy; Tran Viet Thuong; Duong Ngoc Binh; Hiroyuki Miyamoto (Metals, 2021)
In this study, in situ Al2O3-reinforced Ti3Al composite was fabricated after 8 h of milling and sintering at 850 °C. A mixture of TiO2 and Al powders were mechanically milled in a planetary mill, cold-compacted and sintered under a protected argon atmosphere. The microstructure and microhardness of the Al2O3 embedded in Ti3Al matrix at both room and elevated temperature has been reported. The obtained results showed that the Ti3Al/Al2O3 composite was successfully synthesized via the powder metallurgy method. Ti3Al phase and Al2O3 particles were formed after 8 h of milling and sintering at 850 °C. The microstructure formation of round and uniformly distributed Al2O3 particles in the Ti3Al matrix improved the microhardness of the composite. At normal temperature, the microhardness of the material measured about 11.5 GPa. Meanwhile, at elevated temperatures, from 600 to 800 °C, it decreased from 4.18 GPa to 3.15 GPa.